2009
DOI: 10.1002/cncr.24595
|View full text |Cite
|
Sign up to set email alerts
|

The role of salvage surgery in patients with recurrent squamous cell carcinoma of the oropharynx

Abstract: BACKGROUND: The objective of this study was to comprehensively review overall survival, functional outcomes, and prognostic factors in patients who underwent salvage surgery for locally recurrent squamous cell carcinoma of the oropharynx (SCCOP) after initial radiotherapy. METHODS: The authors retrospectively reviewed 1681 consecutive patients who completed definitive therapy for primary SCCOP and identified 168 patients with locally recurrent SCCOP who underwent salvage surgery (41 patients), reirradiation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
256
2
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(290 citation statements)
references
References 34 publications
16
256
2
16
Order By: Relevance
“…This may be difficult to achieve in previously irradiated patients as the extent of disease may be difficult to evaluate even with ''state of the art'' imaging studies. Although recent advances in reconstructive procedures have increased the feasibility of larger resections for recurrent HNSCCs, these procedures are associated with significant morbidity [1,6,7] and economic costs [1,8]. These issues are important in consideration of cost-effectiveness.…”
mentioning
confidence: 99%
“…This may be difficult to achieve in previously irradiated patients as the extent of disease may be difficult to evaluate even with ''state of the art'' imaging studies. Although recent advances in reconstructive procedures have increased the feasibility of larger resections for recurrent HNSCCs, these procedures are associated with significant morbidity [1,6,7] and economic costs [1,8]. These issues are important in consideration of cost-effectiveness.…”
mentioning
confidence: 99%
“…A median survival of 9.7 months and 13.1 months for BNCTtreated patients with recurrent HNC was reported in two out of the 7 eligible trials (Kankaanranta et al, 2012;Suzuki et al, 2014). This is an improvement from an estimated lifespan of 6 months had these patients been offered supportive care only (Zafereo et al, 2009). Median survival could not be reported in the other 5 trials because a large proportion of the patients were still alive at the study end-point.…”
Section: Discussionmentioning
confidence: 97%
“…Only 2 studies reported on progression-free survival (up to 7.9 months) (Kankaanranta et al, 2012;Suzuki et al, 2014). This end-point is important for these patients, as head and neck tumours may cause a loss of organ function and cosmesis issues that may impair the patients' quality of life (Zafereo et al, 2009). Generally these radioresistant recurrent head and neck tumours, responded well to BNCT with at least 71.2% of the patients experiencing tumour shrinkage of more than 30% or complete disappearance of tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate of salvage surgery after intensive chemoradiation therapy for patients with head and neck cancer was reported to be 11%-63.2% [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Salvage surgery is generally attempted, when localized persistent or recurrent primary tumors are observed after initial chemoradiotherapy [9][10][11][12]. However, there have been no reports of salvage surgery for patients with persistent/recurrent maxillary sinus cancer after intensive chemoradiotherapy to date.…”
Section: Introductionmentioning
confidence: 99%